شكوى الدّهر في أشعار جاهليّة - ستيتي لارا عدنان (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يتناول هذا البحث تجلّيات شكوى الشّاعر الجاهليّ من الدّهر ، وذلك من خلال مظاهر شقائه وعجزه ؛ فشكا الدّهر الّذي تجلت قواه السّالبة في صورتي الطّلل والعجز. وسنتبين حقيقة الألم الّذي أَلَمَّ بالجاهليّ في لحظات وقوفه الفنّي أمام الطّلل؛ مشيراً إلى رعب طالما حاول رسم أبعاده تفريغاً لهمّ ، أو تمهيداً لأمرٍ ما ، وما هذا الرّعب سوى الدّهر، كما سنجد في هذا البحث إحساس العجز، ومحاولة الجاهليّ التّغلب عليه تارةً ، والاستسلام للواقع تارة أخرى ، فما العجز إلاّ فقدان قدرة الإنسان، واستحالة تحقيقه لفعلٍ يريد القيام به ، وإذا وقف المرء عاجزاً أمام المرض والموت والفراق، فإن أشد ما أحسّ به عجزه على مقاومة القدر. تبدأ الدّراسة بالحديث عن مفهوم الدّهر، ثم نظرة الشّعراء الجاهليّين إلى الدّهر، وتبيّن تجلّيات الشّكوى من الدّهر ضمن صورتي الطّلل والعجز. This research deals with the study of the manifestations of the pre-Islamic poet complaint of a lifetime, and through the manifestations of misery and helplessness; complained forever that reflected the negative forces in both picture of ruins and inability. In fact, this points to horror as long he tried to draw a nominally to relax, or to prepare for a specific matter. This horror is no more than time, as we find in this research a sense of impotence, and the al-Jahili tries to overcome it at times, and surrender at others. Impotence means man’s inability, and the impossibility to achieve his goals. If man stops helpless in front of disease, death and loss and others, the most felt thing is his failure to resist fate. This study begins by talking about the concept of eternity, then scrutinizes the al-Jahili poets’ view to fate. It manifests the revelations of complaint from fate with the two pictures of ruins and inability.